2016
DOI: 10.1007/s12017-016-8418-6
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Development of Botanical Polyphenols as “Natural Drugs” for Promotion of Resilience Against Stress-Induced Depression and Cognitive Impairment

Abstract: Extensive evidence has demonstrated that psychological stress has detrimental effects on psychological health, cognitive function, and ultimately well-being. While stressful events are a significant cause of psychopathology, most individuals exposed to adversity maintain normal psychological functioning. The mechanisms underlying such resilience are poorly understood, and there is an urgent need to identify and target these mechanisms to promote resilience under stressful events. Botanicals have been used thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
0
22
0
1
Order By: Relevance
“…Polyphenols. The role of these phytochemicals in brain health and ageing is an emerging area (62)(63)(64) . Large prospective studies have identified associations between the dietary intakes of total or specific polyphenols and cognitive function after up to 13 years of follow-up investigation (65)(66)(67) .…”
Section: Specific Nutrientsmentioning
confidence: 99%
“…Polyphenols. The role of these phytochemicals in brain health and ageing is an emerging area (62)(63)(64) . Large prospective studies have identified associations between the dietary intakes of total or specific polyphenols and cognitive function after up to 13 years of follow-up investigation (65)(66)(67) .…”
Section: Specific Nutrientsmentioning
confidence: 99%
“…Komponen (-)epicatehin merupakan keunggulan coklat karena perannya dalam menetralisir ROS, memblokir produksi ROS, dan menginhibisi aktivitas enzim DNA methyltransferase. 4 Stres merupakan respon otak dan tubuh terhadap tuntutan sehari-hari, seperti sekolah, pekerjaan, kejadiankejadian traumatik, dan lain-lain. 5 Paparan kronik dari stres dapat melemahkan sistem imun dan meningkatkan risiko serangan penyakit infeksi dan memperlambat masa penyembuhan penyakit.…”
Section: Pengaruh Pemberian Coklat (Theobroma Cacao) Terhadap Kualitaunclassified
“…Although positive effects of cocoa polyphenols on mood were reported in one small study of 87 middle‐aged participants (Pase et al . ), the evidence from human studies is generally scarce and expert groups have called for further co‐ordinated research in this area (Ward & Pasinetti ).…”
Section: Specific Nutrients and Brain Healthmentioning
confidence: 99%
“…In the case of depression, animal studies have shown anti-depressant effects of numerous polyphenols, postulated to be related to their anti-inflammatory and neurotransmitter modulation roles (Pathak et al 2013). Although positive effects of cocoa polyphenols on mood were reported in one small study of 87 middle-aged participants (Pase et al 2013), the evidence from human studies is generally scarce and expert groups have called for further coordinated research in this area (Ward & Pasinetti 2016).…”
Section: Polyphenols and Vitaminsmentioning
confidence: 99%